Women in Airbnb: a neglected perspective - Farmaki, Anna (My University, 2019)
This research note examines the perspectives of women with regard to their motives for engaging in peer-to-peer (P2P) accommodation and their practices in mitigating perceived risk. In so doing, semi-structured interviews with 12 female hosts and 18 female guests on Airbnb were performed. Findings reveal that gendered risk is not exclusive to solo female travellers but extends to female hosts who are left more vulnerable to risk as a result of Airbnb’s anti-discriminatory policy. Within this context, the study identifies several tactics that are undertaken by female hosts and guests in mitigating risk, thus highlighting the importance of gender in determining the host-guest relationship within P2P accommodation. In acknowledging that gendered risk is heightened in P2P accommodation settings due to the intimacy of the transaction and the lack of regulatory framework, this research note contributes to the impetus to bring women’s voice in the evolving, dynamic landscape of tourism research.
Keywords: Airbnb; Gendered risk; Guests; Hosts; Women